Rural Development Practices in Nepal - Khatri, Chakra Bahadur (Nepal Journal of Multidisciplinary Research, 2019)
There is great values of rural development programmes in rural country like Nepal. The proper development programmes can get access as the milestone to the livelihood of rural poor and sustainable development of the Nation. This paper tries to carry out the sketch of rural development practices in Nepal. The paper is based on secondary data provided by the different government institutions. Most of the data are obtained from various periodic plans, books, articles, policies of governments. The relevancy of this paper goes to find out the past experiences and to adopt the future guideline for the formulation of effective, popular and sustainable programmes for rural development.